Study the Prevalence of Helicobacter pylori Infection by Different Diagnostic Methods - N. Saeed, Ibtihal; I. Ibrahim, Aseel (Iraqi Journal of Pharmaceutical Sciences, 2017)
A total of 41 patients with gastro duodenal symptoms (show signs of inflammation with or without duodenal ulcer) . 21 males (51.2%) and 20 female (48.8%) with an average age 0f (20 – 80) years old under going gastrointestinal endoscopy at Baghdad teaching hospital in internal disease clinical laboratory , between (February – June) 2009 . Biopsies specimen of antrum , gastric fundus ,& duodenal bulb were examined by the following methods (rapid urease test , Giemsa stain section to detect bacteria , & Haematoxilin and Eosin stained section for pathological study which are considered the gold standard methods , sera or plasma from these patients were tested by immunochromotography (ICM),serological method for IgG antibodies to H. pylori. History picture are( use of certain medication , tobacco , alcohol, and current infection are taken). The results showed that the percentage of prevalence (positive results)were (83%) by histopathological method while it gave only(73%) by serological method and(66%) by rapid urease test, and the prevalence in males was more than in females (44%), (39%)respectively ,and also the prevalence increase with age (40 – 60) 14 out of 15, most patients show gastritis and duodenal ulcer, 25 (60%) by endoscopy diagnosis and 7 (17%) show malignant cancer ,while 9(22%) without any symptoms. The sensitivity of urease test (82%) and specificity (88.1%) and by ICM sensitivity (86%) and specificity (67%) comparing with gold standard methods 100% . The aim of this study is to compare the different diagnostic techniques of Helicobacter pylori infection by using invasive methods (histological examination of gastric & duodenal biopsies stained by Giemsa &Haematoxilin & Eosin methods , & rapid urease test which is considered the gold standard methods & non-invasive serological methods such as ICM rapid test , all these tests provide information about the incidence and prevalence of H. pylori in population , diagnostic value for each test also the eradication of person. Keywords: Serology, Helicobacter pylori , gastric ulcer , Diagnosis